Mental health, disability, and social inequalities : quantitative and qualitative approaches before and after the economic recession in Portugal - Antunes, Ana Filipa Coelho (2018)
Background: Mental disorders present a pressing global health issue, and the disability associated with these conditions poses a challenge to persons’ wellPbeing, daily functioning, work performance, and social inclusion. Subsequently, a lower labour force participation of people with mental disorders has been found due to higher unemployment rates, sickness absence, and early retirement, leading to substantial personal and societal costs. In Portugal, the 2008 economic recession may have contributed to this pattern due to the deterioration of socioeconomic conditions, widening social inequalities in mental health across the population. Following three research phases, this doctoral thesis aimed to provide a better understanding of the consequences of mental disorders, in terms of disability and social inequalities, using both quantitative and qualitative approaches. In the 1st phase, the association between disability and mental disorders was characterized, along with the effect of socioeconomic position in the disability reported by people with mental disorders. Changes in socioeconomic position among people with mental disorders during the economic recession were evaluated in the 2nd phase. Primary health care users and professionals’ perspectives on the relationship between mental health and socioeconomic conditions during the economic recession, together with their proposed solutions to improve populations’ mental health, were explored in the 3rd phase. Methods: Data from the National Mental Health Survey (2008/09), a nationally representative crossPsectional survey (n=3849) were used in the 1st phase. Logistic regression models were performed to evaluate the association between disability and 12Pmonth mental disorders, adjusting for gender, age, education, resence of physical disorders and psychiatric comorbidity. Additionally, odds ratios were estimated at the specific values of the main effects and interaction terms between the presence of any 12P month mental disorder and indicators of socioeconomic position, adjusting for age, gender and presence of physical disorders. Data from the National Mental Health Survey FollowPup (2015/16) (n=911) were used in the 2nd phase. Multinomial and logistic recession models were performed to examine the association between the presence of any 12Pmonth mental disorder in 2008/2009 (T0) and selfPreported changes in indicators of socioeconomic position in 2015/2016 (T1), adjusting for age, gender, education and presence of physical disorders at T0. In the 3rd phase, a qualitative study was conducted in primary health care centres of the Lisbon Metropolitan Area during 2016/17. SemiP structured interviews and focus groups with users and professionals were audioP recorded, transcribed and thematic analysis was conducted. Results: In the 1st phase, disability was found to be significantly associated with both 12P month anxiety (OR: 1.88; 95% CI: 1.23P2.86) and mood disorders (OR: 3.94; 95% CI: 2.45P 6.34). Among people with 12Pmonth mental disorders (n=788) participants categorized as “retired or others” and those with financial deprivation had two times higher odds of reporting disability, when compared with those working (OR=2.19; 95%CI: 1.06P4.48) and nonPfinancially deprived (OR=2.36; 95%CI: 1.31P4.24), respectively. In the 2nd phase, participants with any 12Pmonth mental disorder in T0, when compared to those without these conditions, reported 2.20 (95%CI: 1.31P3.71; p<0.01) higher odds of financial hardship related to daily life in T1. In the 3rd phase, the narratives obtained by users and professionals on the relationship between socioeconomic conditions and mental health during the economic recession encompassed two themes. Poor mental health was perceived as a consequence of adverse socioeconomic conditions, whereas the experience of mental health problems was considered to lead to loss of socioeconomic position, due to disability, sickness absence and early retirement. Lastly, solutions to address the mental health consequences of the economic recession included increasing investment and reversing austerity measures in health and social sectors, enhancing coordination and integration of mental health care, and reducing social inequalities in mental health. Conclusions: The findings of this doctoral thesis contributed to a better understanding on the consequences of mental disorders, focusing on disability and pointing to the impact of the economic recession widening social inequalities in mental health. The cyclical nature of economic recessions urges the need to guarantee socioeconomic protection, access to appropriate healthcare and welfare benefits for people with mental disorders. Moreover, investing in mental health allow paving the way towards more just and equitable societies, a vision that should be promoted along with policy efforts integrating all relevant stakeholders.